Teachers’ Perception and Experience of English as a Medium of Instruction in Nepali Community Schools - Gautam, Ganga; Poudel, Tikaram (Nepalese Linguistics, 2025)
This study explores how basic level teachers perceive and experience the use of English as a Medium of Instruction (EMI) in under-resourced community schools in Nepal. We conducted this qualitative interpretative research adopting a narrative inquiry research design. For this, we selected four participants from under-resourced community schools in Dang district who had observed and experienced the phenomena. We collected data and information through in-depth interviews with the participants. The findings reveal that implementing EMI in under-resourced community schools is highly challenging due to a lack of adequately qualified teachers, low proficiency of the teachers in English and limited resources to manage the EMI classrooms effectively. Moreover, basic level teachers, without having an academic background in English, often face greater challenges and difficulties in adopting EMI. The study also highlights the lack of adequate training and professional development supports for the teachers, further complicating the transition to EMI.